2010
DOI: 10.1128/jcm.01640-09
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Performance Characteristics and Clinical Utility of a Novel Assay for Total Hepatitis C Virus Core Antigen Quantification

Abstract: The detection and quantification of hepatitis C virus (HCV) core antigen in serum or plasma by the use of different assay formats have previously been shown to represent useful markers of viral replication. In the present study, the intrinsic performance characteristics and the potential clinical utility of a novel assay for the quantification of total HCV core antigen were comprehensively assessed by using clinical serum samples and specimens contained in various evaluation panels. The Architect HCV Ag assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
66
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 41 publications
20
66
2
6
Order By: Relevance
“…This need for retesting is a disadvantage of the HCV RNA test. In addition, nucleic acid amplifications are labor-intensive and time-consuming methods and have the risk of laboratory contamination; for these reasons, amplification methods are not suitable for widespread use in most laboratories, especially in developing countries (1,4,11,23,27). Therefore, the HCV Ag assay is needed as a supplemental or preconfirmatory test to preconfirm anti-HCV results and distinguish false-positive results from the accurate ones because it is easy to perform and reliable, has high specificity and sensitivity rates, is cost-effective, is able to shorten the duration of the time to diagnosis of infection in patients during the window period, and has a lower risk of laboratory contamination than assays based on nucleic acid amplification technology (31,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This need for retesting is a disadvantage of the HCV RNA test. In addition, nucleic acid amplifications are labor-intensive and time-consuming methods and have the risk of laboratory contamination; for these reasons, amplification methods are not suitable for widespread use in most laboratories, especially in developing countries (1,4,11,23,27). Therefore, the HCV Ag assay is needed as a supplemental or preconfirmatory test to preconfirm anti-HCV results and distinguish false-positive results from the accurate ones because it is easy to perform and reliable, has high specificity and sensitivity rates, is cost-effective, is able to shorten the duration of the time to diagnosis of infection in patients during the window period, and has a lower risk of laboratory contamination than assays based on nucleic acid amplification technology (31,28).…”
Section: Discussionmentioning
confidence: 99%
“…If both retest values indicate that the specimen is nonreactive, the specimen is considered nonreactive for HCV Ag. If one or both of the duplicates have values of Ն3.00 fmol/liter, the specimen is considered repeatedly reactive (16,23).…”
Section: Methodsmentioning
confidence: 99%
“…The present study focused on the evaluation of the HCV cAg in relation to HCV RNA by real-time RT-PCR, thus we could not assess the effect of antiviral therapies on levels of HCV cAg and this agreed with (Ross et al, 2010), while Veillon et al (2003), concluded that the total HCV cAg assay is a useful test for the detection of HCV viremia and the monitoring of patients treated with IFN alone or in combination with ribavirin.…”
Section: Discussionmentioning
confidence: 89%
“…It is time consuming and expensive. 18,38 HCV RNA is extensively used to confirm antibodybased screening test results. Amplification methods (target amplification by RT-PCR, transmission-mediated amplification (TMA), and signal amplification by b-DNA-branch-DNA are the most expensive methods (45-50 USD per test for real-time PCR, 10-12 USD per test for HCV Ag CIA, and 5-6 USD per test for anti-HCV CIA) when compared with anti-HCV and HCV Ag tests; and require sophisticated technical equipment and highly trained personnel.…”
Section: Molecular Diagnostic Systems and Reactives Used For The Hcvmentioning
confidence: 99%
“…for these reasons, amplification methods are not suitable for wide use in most laboratories, especially in developing countries. 2,10,24,38,44 HCV Genotyping assay. HCV has six genotypes represented by digits (1-6) and multiple subtypes represented by letters (a, b, c…) and most recently a seventh HCV genotype have been characterized.…”
Section: Molecular Diagnostic Systems and Reactives Used For The Hcvmentioning
confidence: 99%